Interactions between genotype and environment drive the metabolic phenotype within Escherichia coli isolates. (11th May 2015) - Sabarly, Victor; Aubron, Cécile; Glodt, Jérémy; Balliau, Thierry; Langella, Olivier; Chevret, Didier; Rigal, Odile; Bourgais, Aurélie; Picard, Bertrand; de Vienne, Dominique; Denamur, Erick; Bouvet, Odile; et al.
Summary: To gain insights into the adaptation of the E scherichia coli species to different environments, we monitored protein abundances using quantitative proteomics and measurements of enzymatic activities of central metabolism in a set of five representative strains grown in four contrasted culture media including human urine. Two hundred and thirty seven proteins representative of the genome‐scale metabolic network were identified and classified into pathway categories. We found that nutrient resources shape the general orientation of metabolism through coordinated changes in the average abundances of proteins and in enzymatic activities that all belong to the same pathway category. For example, each culture medium induces a specific oxidative response whatever the strain. On the contrary, differences between strains concern isolated proteins and enzymes within pathway categories in single environments. Our study confirms the predominance of genotype by environment interactions at the proteomic and enzyme activity levels. The buffering of genetic variation when considering life‐history traits suggests a multiplicity of evolutionary strategies. For instance, the uropathogenic isolate CFT073 shows a deregulation of iron demand and increased oxidative stress response.